The Effect of Self-Regulation Strategy Training on Reducing the Symptoms of ADHD among Cycle One Students in Oman - Dr. Dawood Al Hamdani, Musabah Al Breiki, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Teachers and parents face many challenges that hinder the flow of the educational process at school. One of these challenges is how to deal with attention deficit and hyperactivity disorder (ADHD) students and how to increase their attention and decrease their ADHD symptoms while studying or even in their own life. Similarly, parents find it difficult to deal with these students and keep them calm and focused. In Oman, there is a dearth of research on how to treat ADHD students using educational and psychological solutions. Most of the treatments are previously done clinically and with the help of therapists at hospitals. This pilot study was conducted to assess the effect of suggested strategies which are argued to reduce hyperactivity disorders and increase attention for ADHD students. This strategy is called self-regulation strategy training, and it is claimed that a deficit of self-regulation is essentially pertinent to increase ADHD symptoms (Barkley, 1997). The pilot study fundamentally focused on training six ADHD students, identified by the Teachers and Parents' Conners' scales, to self-regulate their behaviours and thoughts using planning, monitoring and evaluation activities as suggested by Zimmerman (2000) for eight weeks. The finding of this study provides promising results for future projects. In this pilot study, teachers and parents hold positive perceptions towards the intervention through the qualitative data, and the Teachers and Parents' Conners' scales provided a noticeable decrease in the symptoms of ADHD. However, more studies are encouraged to provide more valid and reliable results..